2019
DOI: 10.3233/jhd-180340
|View full text |Cite
|
Sign up to set email alerts
|

Visual Dysfunction in Huntington’s Disease: A Systematic Review

Abstract: It is well-documented that patients with Huntington's Disease exhibit specific deficits in visual cognition. A less well-documented literature also exists that suggests people with Huntington's Disease experience a number of disease-related changes to more rudimentary sensory visual processing. Here, we review evidence for the effects of Huntington's Disease on the integrity of the early visual pathways in humans along with changes to low-level visual sensitivity. We find evidence for reduced structural and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In recent years, retinal thinning has become heavily associated with neurodegenerative diseases of the brain (Helmer et al, 2013;Sivak, 2013). There have been correlations established between retinal thinning and Alzheimer's disease (Chiquita et al, 2019;Cipollini et al, 2019;den Haan et al, 2019), Parkinson's disease (Ahn et al, 2018;Satue et al, 2018), Huntington's disease (Dhalla et al, 2019), Amyotrophic lateral sclerosis (Hubers et al, 2016;Mukherjee et al, 2017), and a case has been reported of reduced retinal thickness after an occipital lobe infarction (Tanito and Ohira, 2013). Given this, it is important that we consider exploring biomarkers of the retina as possible routes of monitoring and diagnosing these debilitating neurodegenerative diseases.…”
Section: Rhodopsin and Retinal Degenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, retinal thinning has become heavily associated with neurodegenerative diseases of the brain (Helmer et al, 2013;Sivak, 2013). There have been correlations established between retinal thinning and Alzheimer's disease (Chiquita et al, 2019;Cipollini et al, 2019;den Haan et al, 2019), Parkinson's disease (Ahn et al, 2018;Satue et al, 2018), Huntington's disease (Dhalla et al, 2019), Amyotrophic lateral sclerosis (Hubers et al, 2016;Mukherjee et al, 2017), and a case has been reported of reduced retinal thickness after an occipital lobe infarction (Tanito and Ohira, 2013). Given this, it is important that we consider exploring biomarkers of the retina as possible routes of monitoring and diagnosing these debilitating neurodegenerative diseases.…”
Section: Rhodopsin and Retinal Degenerationmentioning
confidence: 99%
“…Should screening become possible at earlier stages, clinicians can better intervene in the progression of these diseases. Retinal alterations have recently been associated with numerous neurodegenerative diseases (Helmer et al, 2013;Sivak, 2013;Tanito and Ohira, 2013;Hubers et al, 2016;Mukherjee et al, 2017;Sudharsan et al, 2017;Ahn et al, 2018;Satue et al, 2018;Chiquita et al, 2019;Cipollini et al, 2019;den Haan et al, 2019;Dhalla et al, 2019). Rhodopsin, a G-protein coupled receptor in the rod cells of the retina is a biomarker associated with retinal thinning and degeneration (Cideciyan et al, 2005;Xiong and Bellen, 2013), suggesting its potential in the early detection and progression monitoring of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in neuronal connectivity associated with increased atrophy and decreased neuronal function were observed in the associative visual cortical regions of HD patients [108]. V1 did not exhibit group differences in vascular activity and cortical thickness between early and advanced HD patients; however, significant thinning of the associative visual cortex was correlated with decreased visual perception [108,109]. It appears that V1 remains largely preserved both in its structural and functional form, despite the presence of atrophy in the early stages of HD.…”
Section: Circuit Mechanisms For Normal and Diseased Aging Of Visual Fmentioning
confidence: 93%
“…In Huntington's disease (HD), structural and functional alterations of the visual cortex and visual cognitive deficits are present in both early and advanced stages of the disease [108,109]. A decline in both structural and functional integrity of the visual pathways are characterized by cell loss, cortical thinning, retinal thinning, decreased visually evoked potential amplitude, and decline in second-order visual perceptual and motor abili-ties [108,109]. Neuroimaging studies have shown atrophy of the striate cortex in HD to be one of the major sources for motor deficits and thinning of the visual cortex in HD to be associated with cognitive performance of visuospatial tasks [108].…”
Section: Circuit Mechanisms For Normal and Diseased Aging Of Visual Fmentioning
confidence: 99%
“…Key changes to the visual system, including retinal thinning, temporal retinal nerve fiber layer thinning, loss of retinal ganglion cells, reduced visual evoked potentials, impaired color vision, and poor motion perception, have been evidenced in patients suffering from HD [ 17 , 18 , 19 , 20 ]. Retinal dysfunction and degeneration were evidenced in rodent and Drosophila models of HD [ 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%